2022
DOI: 10.1186/s12885-022-09509-0
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the associations between clinical factors and outcomes by machine learning, using post marketing surveillance data of cabazitaxel in patients with castration-resistant prostate cancer

Abstract: Background We aimed to evaluate relationships between clinical outcomes and explanatory variables by network clustering analysis using data from a post marketing surveillance (PMS) study of castration-resistant prostate cancer (CRPC) patients. Methods The PMS was a prospective, multicenter, observational study of patients with metastatic, docetaxel-refractory CRPC treated with cabazitaxel in Japan after its launch in 2014. Graphical Markov (GM) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…Findings from our study supported a machine learning analysis of cabazitaxel therapy in mCRPC, which suggested association of better OS with neutropenia development and higher number of cabazitaxel cycles ( 12 ). Other patient factors were dependent on the set threshold for correlation—at a higher threshold (0.05), liver metastases, ECOG PS, TTF and neutropenia were associated with OS.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Findings from our study supported a machine learning analysis of cabazitaxel therapy in mCRPC, which suggested association of better OS with neutropenia development and higher number of cabazitaxel cycles ( 12 ). Other patient factors were dependent on the set threshold for correlation—at a higher threshold (0.05), liver metastases, ECOG PS, TTF and neutropenia were associated with OS.…”
Section: Discussionsupporting
confidence: 82%
“…Other patient factors were dependent on the set threshold for correlation—at a higher threshold (0.05), liver metastases, ECOG PS, TTF and neutropenia were associated with OS. Apart from neutropenia, the same was true at a lower threshold (0.01) ( 12 ).…”
Section: Discussionmentioning
confidence: 76%
“…Machine learning is intended to use these as sources of information for the prevention, early diagnosis, and treatment of diseases. The number of machine learning papers is increasing in a variety of areas, such as predicting the side effects of drugs in older adults, predicting side effects of anticancer drugs, and correlating survival with clinical data (8)(9)(10). The number of reports on machine learning in oncology has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The measures taken as alternatives to maintain the functioning of teaching have been multiple, mediated by the use of technological tools and resources that have left consequences and results that need to be carefully analyzed and taken into account. Kazama et al, (2022) in that it alludes to the visions about the actions to be implemented for the recovery, adjustment and achievement of the university processes with the positive and negative consequences of the whole stage of the pandemic. An assessment is made of possible stages or phases of development with the idea of determining these results and the implementation by way of strengthening the mediation of Information and Communication Technologies, and the perspectives of the student body and the teaching staff for the improvement of their performance.…”
Section: Introductionmentioning
confidence: 99%